STRATEGI PEMBANGUNAN PERMUKIMAN KUMUH MELALUI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KOTA DENPASAR (STUDI KASUS : KECAMATAN DENPASAR UTARA, KOTA DENPASAR, PROVINSI BALI) - Widiantari, Ni Ketut; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2021)
North Denpasar District is a sub-district that has the largest area of ??slum settlements, reaching 38,2353 hectares or about 46% of all slum settlements in Denpasar City. However, in its handling through the Program KOTAKU there are still problems. In improving and making strategies, a strategy analysis is needed using indicators of strategic management processes according to Wheelen and Hunger and also SWOT analisis techniques according to Freddy Rangkuti. The research uses descriptive qualitative research methods. This study produces an alternative strategy SO (Strength-Opportunities) in the form of seven alternative strategies. Four strategies have been described above which are the priority scale of the Program KOTAKU namely improving the handling of slums with the existing objectives using a collaboration platform, optimizing the role of the city government as a skipper to increase collaboration with CSR, maximizing the performance of the Pokja PKP, and optimizing support from the central government. Keyword : Program Kota Tanpa Kumuh (KOTAKU), strategic management process, SWOT analysis